2019
DOI: 10.1177/0957926519828030
|View full text |Cite
|
Sign up to set email alerts
|

Too good to be true: The effect of conciliatory message design on compromising attitudes in intractable conflicts

Abstract: The aim of this article is twofold: first, to demonstrate how the use of experimental methods challenges the implicit assumption of progressive discourse analysts that ‘inspiring’ messages will have a positive effect on political attitudes and trust regardless of the recipients’ early political dispositions, and second, to examine the power of conciliatory message design to change political attitudes in favor of a peaceful solution to intractable conflicts such as the Israeli–Palestinian conflict. By employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Such contradictory outcomes following amicable messages have been documented in the past in the context of the Israeli–Palestinian conflict (Cohen-Chen et al, 2014; Kampf & David, 2019), which serves as the case study for the current exploration. This conflict was chosen because it allowed us to collect a large number of unexpected amicable statements made by controversial foreign leaders.…”
Section: Evaluation Of (Amicable) Messages In Conflicts: What Do We Kmentioning
confidence: 99%
See 4 more Smart Citations
“…Such contradictory outcomes following amicable messages have been documented in the past in the context of the Israeli–Palestinian conflict (Cohen-Chen et al, 2014; Kampf & David, 2019), which serves as the case study for the current exploration. This conflict was chosen because it allowed us to collect a large number of unexpected amicable statements made by controversial foreign leaders.…”
Section: Evaluation Of (Amicable) Messages In Conflicts: What Do We Kmentioning
confidence: 99%
“…Studying the emotional factor, Cohen-Chen et al (2014) found that when encountered with information from the opposing group that opens an opportunity for initiation of a peace process, a sense of fear of the “enemy” will lead to selective exposure to information, which can thwart its conciliatory potential. Other receiver-oriented factors include political leaning, beliefs about the possibility of achieving lasting peace, perception of the conflict’s uniqueness, worldviews, general values (i.e., traditionalism) and conflict-specific societal beliefs (i.e., delegitimization of the out-group, sense of collective victimhood; see Kampf & David, 2019; Kudish et al, 2015). These factors can obstruct openness to new information about adversaries (Halperin & Bar-Tal, 2011) and willingness to make concessions (Kudish et al, 2015).…”
Section: Evaluation Of (Amicable) Messages In Conflicts: What Do We Kmentioning
confidence: 99%
See 3 more Smart Citations